PENGARUH PENGETAHUAN INVESTASI, MODAL AWAL INVESTASI DAN SOSIAL MEDIA INFLUENCER TERHADAP MINAT BERINVESTASI MAHASISWA DI PASAR MODAL (STUDI EMPIRIS PADA SEKOLAH TINGGI ILMU EKONOMI SURAKARTA) (Lembaga Pengembangan Kinerja Dosen, 2023)
The reason of this inquire about is to test the affect of introductory speculation capital, speculation information, and social media influencers on students' intrigued in contributing within the capital advertise. The investigate populace was all dynamic understudies at STIE Surakarta, both majoring in bookkeeping and administration, and the test was taken utilizing the slovin strategy, 96 understudy tests were gotten. The information gotten is essential information through surveys with a add up to of 22 questions. Each question was measured employing a 5 Likert scale. The information investigation strategy in this inquire about employments different direct relapse investigation procedures. The investigate comes about clarified that the variable beginning venture capital, speculation information, and social media influencers in part had a positive affect on venture intrigued. At the same time the factors of starting speculation capital, speculation information, and social media influencers have a noteworthy affect on speculation eagerly. Keywords : Initial Investment Capital; Investment Knowledge; Social Media Influencer; investment interest